Neuroanatomy of the Marine Jurassic Turtle Plesiochelys etalloni (Testudinata, Plesiochelyidae) - Paulina Carabajal, Ariana (2013)
Turtles are one of the least explored clades regarding endocranial anatomy with few available descriptions of the brain and inner ear of extant representatives. In addition, the paleoneurology of extinct turtles is poorly known and based on only a few natural cranial endocasts. The main goal of this study is to provide for the first time a detailed description of the neuroanatomy of an extinct turtle, the Late Jurassic Plesiochelys etalloni, including internal carotid circulation, cranial endocast and inner ear, based on the first digital 3D reconstruction using micro CT scans. The general shape of the cranial endocast of P. etalloni is tubular, with poorly marked cephalic and pontine flexures. Anteriorly, the olfactory bulbs are clearly differentiated suggesting larger bulbs than in any other described extinct or extant turtle, and indicating a higher capacity of olfaction in this taxon. The morphology of the inner ear of P. etalloni is comparable to that of extant turtles and resembles those of slow-moving terrestrial vertebrates, with markedly low, short and robust semicircular canals, and a reduced lagena. In P. etalloni the arterial pattern is similar to that found in extant cryptodires, where all the internal carotid branches are protected by bone. As the knowledge of paleoneurology in turtles is scarce and the application of modern techniques such as 3D reconstructions based on CT scans is almost unexplored in this clade, we hope this paper will trigger similar investigations of this type in other turtle taxa